FAKTOR INTERNAL DAN EKSTERNAL TERHADAP KEPUTUSAN PEMBELIAN TELEPON SELULAR MERK NOKIA - -, NASIKAN -; SASMITO, BEGY ANDY (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
Abstract: This study aims to identify and analyze how big the influence of internal factors (perceptions, attitudes, lifestyle, personality) and external factors (cultural, social, reference, situation) on consumer purchasing decisions. This research is analytic research is research that uses inferential statistics to test hypotheses. Analysis tools using a statistical method of multiple linear regression analysis. Data obtained from respondents as many as 223 students. Results of that study, all independent variables were studied simultaneously and has a partial influence on purchasing decisions on mobile phones. Purchasing decisions, internal factors and external factors affect by 27.2%, while the remaining 72.8% were not influenced by other Key words: internal factors, external factors, purchasing decisions